Implementation Research on Cardiovascular Diseases in India: A Systematic Review - Hisham Moosan; Arun Kumar Sharma; Mahendra Thakor; Ansuman Panigrahi; Vikas Dhikav; Suresh Yadav; Ramesh Kumar Huda; Mukesh C. Parmar; Poonam Singh; Suman S. Mohanty; Denny John (Wolters Kluwer Medknow Publications, 2024)
Cardiovascular diseases (CVDs) are the leading cause of death globally and the prevention and control of these diseases tend to entail longer and larger social and economic commitments on the part of governments. This systematic review (SR) aims to understand the quantum, diversity, and quality of implementation research (IR) done in the field of CVDs in India with a view to maximizing the utility of the efforts made by the government. The evidence was collated on IR on CVDs in India conducted in the past 20 years (2001-2021) using a SR approach. The SR was drafted using Preferred Reporting Items for SRs and Meta-analyses guidelines. Academic databases (PubMed, Embase, and Science Direct) and nonacademic databases (Google Scholar and ProQuest) were chosen, along with repositories of gray literature. Retrieved articles were screened for titles and abstracts and assessed by two independent reviewers. The articles also underwent a concomitant risk of bias assessment utilizing checklists (STARI, STROBE, CONSORT, etc.,) and a narrative summary was drafted using SwiM guidelines. In the final analysis, 10 articles that fitted the inclusion criteria of IR for CVD in India were included, of which seven were directed at IR on hypertension, and three were related to coronary artery disease, myocardial infarction, and stroke. Acceptability, adoption, and feasibility were the only attributes of IR that were explored in these studies.